Comparative Analysis of the Factors Necessitating Commercial Banks and Manufacturing Firms’ Involvement in Corporate Social Responsibility in Nigeria - Abiola Idowu; Olu Ojo (Bina Nusantara University, 2016)
This research investigates the factors necessitating commercial banks and manufacturing firms’ involvement in Corporate Social Responsibility (CSR) in Nigeria comparatively. The research took place in Lagos State in South-west geo-political zone in Nigeria. The survey research design was used in this research. Moreover, the purposive sampling was used in selecting five commercial banks and five manufacturing firms. Primary data were gathered with the aid of questionnaire from 216 respondents out of 250 selected respondents from bank and 205 respondents out of 250 selected respondents from manufacturing firms. Fifty copies of the questionnaires were distributed to each company. All respondents selected were involved in CSR activities of their companies. Factors necessitating companies’ involvement in CSR were examined with Analysis of Variance. The research reveals that t-test value is -0.39 and p-value is 0.8, which shows that there is no significant difference between factors necessitating of the commercial banks and manufacturing firms’ involvement in CSR. The research recommends that corporate organizations should give attention to CSR initiatives as these lead to improvement of customers loyalty, improvement of the positive image of the organization, improved relationship with local communities, and enhances shareholders values as well as improved relations with public authorities amongst others.